Sharing the Taiwan experience a brief look at the Republic of China - Chi, Su; Wong, Min-hsiung; Chi, Su (Taiwan : Kuangchi Program Service [production company] ; Taiwan : Kwang Hwa Mass Communications [distributors])
'Taiwan experience' refers to the accomplishments accumulated in recent years by the Republic of China government through reforms and developments in economics, politics, education, culture and environmental protection.
Executive producer, David J.C., Yen S.J. ; photographers, Tsung-ming ke, Kuo-Yu Chian ; music, Taiwan Rock Records Co. LTD ; editor, Chao-hua Lo
Keywords: Economic development -- Taiwan